(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Video Coding Standards such as MPEG, H.26X contains Block Matching Motion Estimation process in Video processing. Finding Motion Vectors are important in Video Compression point of view. Since any video coding techniques can be included after movement estimation. Many quick quest calculations are accessible for Motion Estimation. The proposed algorithm contains a combination of the Adaptive Search Area Selection and the Diamond Search algorithm, which is called the Hybrid ASW-DS algorithm to reduce the processing time of ME. The proposed algorithm is compared to other algorithms by considering parameters such as PSNR, Computations per block and Search Point number.